Assessment of Risk-health Related Behaviors of Female Adolescents and Their Determinants - Abdul Wahid, hala (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: The study aims to assess the female adolescents’ risk-health behaviors, to identify their determinants, to determine the association between the risk health behaviors and the stage of adolescence for these females’ demographic variable. Methodology: A purposive sample of (268) female adolescents is selected from intermediate and secondary schools in Baghdad City. These adolescents have presented the age of (14-19) year old and divided into two groups of (14-16) year and (17-19) year. A questionnaire is constructed for the purpose of the study, it is composed of (10) major parts, and the overall items, which are included in the questionnaire, are (106) item. Reliability and validity of the questionnaire were determined through a pilot study which is carried out during the period of February 15th 2012 through March 15th 2012. The study instrument is used as mean of data collection. The data are analyzed through the application of the descriptive statistical data analysis approach (Frequency and Percentage) and the inferential statistical data analysis (Chi-squared test). Results: The results indicate that the female adolescents have risk-taking behaviors with respect to food consumption and dietary habits. They are physically inactive, and some of them unfortunately is not concerned with the control of their weight, especially, those who are among the late adolescence females. Smoking has a considerable rate among older female adolescents. But most of them is experiencing healthy behaviors relative to drug use. Through the interpretation of their psychological state related behaviors, some of them has presented feelings of sadness and loneliness with suicidal ideas. Even though, they do care about their personal safety, and personal and oral hygiene properly. The most influential determinant of female adolescents’ health related behaviors, that the present study has identified, is the family for the reason that our culture is considered as family-centered ones. Then, the school and the media have become to be less influential determinants. Recommendations: The study recommends that health promotion and protection oriented education programs that address these risk- health behaviors can be designed, structured and presented to the female adolescents for the purpose of motivating and enabling them for better orientation toward healthy behaviors. A nation-wide study can be done to determine variety of healthrelated behaviors that can be used as data base for further research in this area.